Analisis dan Pengembangan Hasil Perbaikan Produktivitas Ritase Haulage di PT. X Cabang Jakarta - Emmanuel Sandy Setjiadi; Iwan Halim Sahputra (Jurnal Titra, 2022)
PT. X had the probem of low haulage productivity in 2021 where the target of 10 ritases per truk per day was often not achieved. The company has made improvements using the DMAIC method. This study aims to provide an analysis of the achievement, control, and development of productivity improvements in haulage trucking. Data collection techniques were carried out using observation, interviews, and company past data. Data processing was done by histograms, T statistical test, and control chart. From the results of the study, it is knon that the T-test shows that conditions before the repair have been validated and are not better than the conditions after the repair. The I-MR chart shows that the improvement after the repair process is stable and maintained within the existing UCL and LCL. Truck availability increased 7,15% to 92,44%. Driver availiability increased 3% to 94%. Ritase achievement increased by 25,01% to 12,15 ritase/truck.